Determinants of higher education demand in Colombia, 1980-2010 (2013)
The objective of this article is to analyze the main microeconometric factors that correlate with the demand for higher education in Colombia, using data from the ENH and ECH (GEIH) surveys carried out by the DANE and through the estimation of robust discreet choice models. The results show the importance of gender, parents' educational level and work status, family composition and income in the demand for higher education. All these variables determine the fact that the principle of equal education opportunities is not fulfilled, as pointed out by Barr (1993).